Self-monitoring, Cultural Training and Prior International Work Experience as Predictors of Cultural Intelligence - a Study of Indian Expatriates - Gupta, BIndu; Singh, Davinder; Jandhyala, Kaushik; Bhatt, Shweta (Organizations and Markets in Emerging Economies, 2013)
The present study examined the role of self-monitoring, expatriate training, and prior international work experience on the cultural intelligence of expatriates. The data was collected from 223 Indian expatriates through a questionnaire survey. The results of data analysis indicated that self-monitoring has a significant impact on the cultural intelligence of the expatriates. Further analysis was done to examine the effect of these independent variables on individual dimensions of cultural intelligence. The findings signify that self-monitoring has a significant effect on all the three cultural dimensions, namely, cognitive, emotional/motivational and behavioral, and that expatriate training has a significant impact on the emotional/motivational dimension, but not on the other two. Prior international work experience was found not to have a significant effect on cultural intelligence and its dimensions. These findings provide significant insights into organizations for selecting and training the expatriates leading to their effective adjustment and performance in a different culture context. This paper contributes to expatriate management literature highlighting the effect of personality variables along with expatriate training. Further, it is a contribution to the research in cultural intelligence which is a relatively nascent area of research.